Perinatal Management of Pregnancy Complicated by Autosomal Dominant Emery-Dreifuss Muscular Dystrophy - Megumi Sato; Hiromitsu Shirasawa; Kenichi Makino; Hiroshi Miura; Wataru Sato; Dai Shimizu; Naoki Sato; Jin Kumagai; Akira Sato; Yukihiro Terada (Thieme Medical Publishers, Inc., 2016)
Abstract Introduction Autosomal dominant Emery-Dreifuss muscular dystrophy (AD-EDMD) is rare compared with other forms of muscular dystrophy and is characterized by cardiac conduction defects. Here, we present the case of a patient diagnosed with AD-EDMD during the first trimester of pregnancy who developed acute preeclampsia and subsequently, congestive heart failure (CHF) following cesarean section. Case A 36-year-old, gravida 0 para 0 woman was diagnosed with AD-EDMD by genetic testing during the first trimester of pregnancy, and she suddenly developed preeclampsia and partial HELLP (hemolytic anemia, elevated liver enzymes, and low platelets) syndrome at 33 weeks of gestation. The patient subsequently developed CHF following cesarean section. Conclusion CHF can occur as a direct result of the cardiac defects arising due to EDMD, and therefore, careful prenatal and postpartum management is recommended for such cases.